Drying Characteristics and Analysis of Heat and Mass Transfer of Industrial Iron Powder at Low Temperature and Low Pressure - Zhang Ruhang; Liu Jianhua; Zhang Liang; Lin Jindi (Zhileng xuebao)
In this study, a low-temperature and low-pressure heat pump drying device was built to explore the drying effect of industrial iron powder at different low pressures and analyze the heat and mass transfer in the low-temperature and low-pressure drying processes. The results show that a decrease in the drying ambient pressure can increase the dehumidification capacity of wet iron powder. When the ambient pressure drops from 101 kPa to 10 kPa, the dehumidification capacity increases by 2.5 times, and the moisture content of iron powder can be reduced to less than 1% at a pressure of 10 kPa. For drying air at 50 °C and 0.5 m/s, the mass and heat transfer coefficient decrease by 28.1% and by 68.4%, respectively, as the pressure decreases from 101 kPa to 10 kPa. Therefore, the Lewis factor, which characterizes the relative intensity of heat and mass transfer, can increase with the ambient pressure decrease. In a drying environment of 10 kPa and 50 °C, the mass and heat transfer coefficient increase by 32.9% and 67.8%, respectively, when the air speed increases from 0.2 m/s to 2 m/s. This indicates that the enhanced effect of air speed on the mass transfer coefficient is inhibited by the low-pressure environment; thus, the Lewis factor increases with the increase in air speed. The Lewis factor is 0.5–0.6 in an environment of 10 kPa, indicating that there are obvious differences between the mass diffusion and heat diffusion in a low-pressure environment.